The Age-Specific Association of Waist Circumference and Risk of Chronic Kidney Disease in Patients with Type 2 Diabetes Mellitus in Shandong, China - Lingling Xu; Weihong Yu; Ping Huang; Chunying Li; Yan Li; Meng Wang; Qun Xu; Jing Wang; Caixia Zheng; Bin Qu; Yanping Zhao; Meng Niu; et al. (International Journal of Endocrinology)
Objective. To examine the association of three most common obesity measures including body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) with chronic kidney disease (CKD) risk in patients with type 2 diabetes mellitus (T2D). Design. Cross-sectional evaluation of the effect of anthropometric measures on CKD risk. Setting. Outpatient Department. Subjects. T2D patients who were treated between October 2012 and May 2013. Intervention. None. Main Outcome Measure. CKD risk. Results. On average, the patients had a mean age of 60.2 years, and 40% were males. CKD was present in 46% of all the patients. In multivariate logistic regression using the imputed data, higher WC was associated with greater odds of CKD (OR = 1.019, 95% CI = 1.002–1.006, P=0.030), but not BMI and WHR. Interestingly, we found that patients with very small WC seemed to have greater odds of CKD. We observed age-specific effect of WC such that the effect of WC on CKD risk is significant only in middle-aged T2D patients. Conclusion. Our study provides evidence for the association of WC with CKD in Chinese patients with T2D. T2D patients, especially middle-aged T2D patients, should reduce their WC to decrease CKD risk.